Calibrating the Wildfire Decision Model using hybrid choice modelling - Lovreglio R; Kuligowski E; Walpole E; Link E; Gwynne S (Elsevier Ltd, 2020)
Wildfire occurrences is creating serious challenges for fire and emergency response services and a diverse range of communities around the world due to the increment of the occurrence of these disasters. As such, understanding the physical and social dynamics characterizing wildfires events is paramount to reduce the risk of these natural disasters. As such, one of the main challenges is to understand how households perceive wildfires and respond to them as part of the evacuation process. In this work, the Wildfire Decision Model originally proposed in Lovreglio et al. [1] is calibrated using a hybrid choice model formulation. The Wildfire Decision Model is a newly developed behavioural choice model for large-scale wildfire evacuations based on the estimation of the risk perceived by households and the impact that this has on the decision-making process. This model is calibrated using a hybrid choice modelling solution and survey data collected after the 2016 Chimney Tops 2 wildfire in Tennessee, USA. The proposed model shows good agreement with the preliminary findings available in the wildfire evacuation literature; namely, the perceived risk is affected by both external factors (i.e., warnings and fire cues) and internal factors (i.e., education, previous wildfire evacuation experience and time of residency in a property).
Keywords: Household; Evacuation; Wildfire; Hybrid choice; Modelling; 0502 Environmental Science and Management; 1117 Public Health and Health Services; 1604 Human Geography